Molecular Identification of Aspergillus Species, Antifungal Susceptibility, and Phenotypic Identification of Azole-Resistant Mutations in Cyp51A Gene Isolated from Xinjiang - Yusufu A; Aizezi Z; Nuermaimaiti X; Liu Y; Wang X (Infection and Drug Resistance)
Aikedai Yusufu, Zubaidanmu Aizezi, Xiyidan Nuermaimaiti, Yiting Liu, Xiaodong Wang Department of Dermatology, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, People’s Republic of ChinaCorrespondence: Xiaodong Wang, Department of Dermatology, The First Affiliated Hospital of Xinjiang Medical University, No. 393, Xinyi Road, Urumqi, Xinjiang, People’s Republic of China, Email zhengdong18@sina.comPurpose: This study aimed to determine the clinical distribution characteristics, in vitro antifungal susceptibility, and cyp51A mutation types of clinically isolated Aspergillus species in Xinjiang.Methods: In this study, a total of 111 Aspergillus species were identified by sequencing the internal transcribed spacer (ITS) and β-tubulin (BenA) genes for molecular identification, performed antifungal susceptibility testing on these isolates using Sensititre YeastOne, selected azole-resistant isolates based on the antifungal susceptibility results and amplified the cyp51A gene for identification of the azole resistance mutation phenotype in the selected isolates.Results: The most common Aspergillus species was A. fumigatus (40.54%), followed by A. niger (18.02%), A. tubingensis (16.22%), A. terreus (13.51%), A. flavus (6.31%), A. welwitschiae (2.70%), A. fumigatiaffinis (1.80%), and A. lentulus (0.90%). The antifungal susceptibility test results showed that A. fumigatus, A. niger, A. tubingensis, A. flavus and A. terreus were completely sensitive to itraconazole, with sensitivity rates of posaconazole and voriconazole were 99.10% and 88.29%, respectively. The sensitivity rate to amphotericin B was the lowest (62.16%). The MIC values of amphotericin B and voriconazole for the two cryptic Aspergillus species, A. lentulus and A. fumigatiaffinis with high (> 1mg/L). The azole non-susceptible or non-wild type rate was (15/111, 13.51%). Eleven azole-resistant Aspergillus species had cyp51A mutations, while four strains did not have any cyp51A mutations.Conclusion: In this study, the pathogenic Aspergillus species isolated from clinical cases in Xinjiang were diverse. Common pathogenic species showed the best in vitro antifungal activity against itraconazole, posaconazole, and echinocandins, whereas the MIC distribution of amphotericin B was significantly higher. Resistant strains may be mediated by point mutations in cyp51A, and phenotypic mutations are diverse. This information is of great significance for guiding the early diagnosis and antifungal therapy for aspergillosis.Keywords: invasive aspergillosis, Aspergillus fumigatus, azole-resistance, antifungal susceptibility, cyp51A gene